Upaya Menumbuhkan Kebiasaan Menjaga Kebersihan Lingkungan Sekolah Sebagai Bentuk Pendidikan Konservasi di SDN Kalibanteng Kidul 03 - Wibowo, Cahyo Adi; Nugraheni, Nursiwi (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Environmental education is an important effort in forming awareness and responsible behavior towards the environment, especially in young students. This article highlights the urgency of environmental education in shaping students' behavior towards the environment in elementary schools. Using the literature review method, this research presents an overview of the importance of cleanliness of the school environment, strategies for building student character, and the role of schools in environmental education. The research results show that efforts to maintain a clean school environment involve factors such as teacher example, character education, active student participation, and external support. Programs such as mutual cooperation activities and a picket team system in each class have proven to be effective in forming awareness and positive behavior towards the environment. Thus, maintaining the cleanliness of the school environment is not just a physical task, but also an investment in character building and shared prosperity for the entire school community.